Linguistic Intelligence and Critical Thinking of Students of Inland Water and Ferries Transport Polytechnic of Palembang - Bambang Setiawan; Umi Dian Wulan Ningrum; Dani Dwi Sasongko (LPPM Universitas Jambi, 2020)
This study was carried out to investigate the students’ Linguistic Intelligence (LI) and Critical Thinking (CT) as Higher Order of Thinking Skills (HOTS) in English as foreign language acquisition. Regarding to the study, 70 participants of Inland Water and Ferries Transport Polytechnic of Palembang were taking part in the current study. To measure the participants' linguistic intelligence scores, the researchers used Thomas Armstrong Intelligence Test derived from Howard Gardner’s MI Model. The instrument consists of 20 Likert type questions, for each of which 4 options are considered questionnaire. When testing participants' critical thinking, they used the scheme and the measures that trail after Watson-Glaser Critical Thinking Appraisal® and are alike. This test consists of five parts that are inferences, assumptions, deductions, interpreting information, and arguments. And the result indicated that were 11.43 percent students who are in the performance of below average and 58.57 percent who are categorized into high linguistic intelligence.